Soil-Transmitted Helminth Vaccines: Are We Getting Closer? - Zawawi, Ayat; Else, Kathryn J. (Frontiers in Immunology, 2020)
Parasitic helminths infect over one-fourth of the human population resulting in significant morbidity, and in some cases, death in endemic countries. Despite mass drug administration (MDA) to school-aged children and other control measures, helminth infections are spreading into new areas. Thus, there is a strong rationale for developing anthelminthic vaccines as cost-effective, long-term immunological control strategies, which, unlike MDA, are not haunted by the threat of emerging drug-resistant helminths nor limited by reinfection risk. Advances in vaccinology, immunology and immunomics include the development of new tools that improve the safety, immunogenicity, and efficacy of vaccines; and some of these tools have been used in the development of helminth vaccines. The development of anthelminthic vaccines is fraught with difficulty. Multiple lifecycle stages exist each presenting stage-specific antigens. Further, helminth parasites are notorious for their ability to dampen down and regulate host immunity. One of the first significant challenges in developing any vaccine is identifying suitable candidate protective antigens. This review explores our current knowledge in lead antigen identification and reports on recent pre-clinical and clinical trials in the context of the soil-transmitted helminths Trichuris, the hookworms and Ascaris. Ultimately, a multivalent anthelminthic vaccine could become an essential tool for achieving the medium-to long-term goal of controlling, or even eliminating helminth infections